The Makna ‘Sakinah’ Dalam Al-Quran Serta Relevansinya Terhadap Kehidupan Berkeluarga Di Era Moderen - Ikhsanudin, Akhmad; Latif, Adri; Meidina, Ahmad Rezy (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2024)
The meaning of the word 'sakinah' has various meanings and points of view. The shift in life values ​​will affect the meaning of the word 'sakinah' itself. This article aims to provide a new perspective on the meaning of 'sakinah' in the context of the modern family. This research is of a qualitative type using the Library Research method which is analyzed descriptively and analytically. From this research it can be concluded that in terms of modern families, family happiness is greatly influenced by several factors, such as financial factors, education, emotional maturity and good communication between husband and wife.